Cocaine self-administration attenuates brain glucose metabolism and functional connectivity in rats - Christopher Rowan; Colin Hanna; Munawwar Sajjad; Rutao Yao; Alireza Sharafsha; Kai-Uwe Lewandrowski; Kenneth Blum; Albert Pinhasov; Panayotis K. Thanos (PLoS ONE, 2025)
Background Cocaine abuse and Cocaine Use Disorder (CUD) is an increasingly urgent public health issue leading to major health risks often resulting in a decreased lifespan and quality of life. Previous human research has described brain function of cocaine addicts however the amount of cocaine use, duration of use, and exclusion of using other drugs (i.e., nicotine and alcohol) have all been difficult to control. One unanswered question is related to how does cocaine affect both brain glucose metabolism and functional connectivity?. Methods The present study examined using positron emission tomography (PET) imaging and the glucose analog [18F]-Fluorodeoxyglucose (18F-FDG), brain glucose metabolism (BGluM) and functional connectivity in male rats (N = 6) that self-administered cocaine compared to baseline control scans in the same animals prior to cocaine exposure. Results Our Results showed that Cocaine Self-Administration (CSA) caused significant BGluM decreases in several brain regions including posterior thalamic nuclei, Claustrum (Cl); Solitary nucleus, Presubiculum (PrS); Caudate Putamen (CPu); Anterior hypothalamic area (AHA); Ventral pallidum (VP); and amygdala. Activation (increased BGluM) was observed in the primary somatosensory cortex. These regions are associated with memory, spatial navigation, visual processing and saliency along with other somatosensory and motor functions, as well as regulatory autonomic function (cardiovascular) and hormonal response. Conclusion This brain functional connectivity mapping illustrated a brain circuit composed of brain regions that are either a part of or connect with the mesolimbic reward pathway that is mediated by dopamine. When this circuit is dysregulated, it is believed to be associated with substance use disorders and reward dysregulation which have recently been described as attributes of preaddiction.